Cutaneous wound healing: An update from physiopathology to current therapies - Gushiken, Lucas Fernando Sérgio [UNESP] (2021)
The skin is the biggest organ of human body which acts as a protective barrier against deleterious agents. When this barrier is damaged, the organism promotes the healing process with several molecular and cellular mechanisms, in order to restore the physiological structure of the skin. The physiological control of wound healing depends on the correct balance among its different mechanisms. Any disruption in the balance of these mechanisms can lead to problems and delay in wound healing. The impairment of wound healing is linked to underlying factors as well as aging, nutrition, hypoxia, stress, infections, drugs, genetics, and chronic diseases. Over the years, numerous studies have been conducted to discover the correct approach and best therapies for wound healing, including surgical procedures and non-surgical treatments such as topical formulations, dressings, or skin substitutes. Thus, this general approach is necessary to facilitate the direction of further studies. This work provides updated concepts of physiological mechanisms, the factors that can interfere, and updated treatments used in skin wound healing.